Is overreliance on short-acting β2-agonists associated with health risks in the older asthma population?. Issue 1 (28th March 2022) - To, Teresa; Zhu, Jingqin; Terebessy, Emilie; Zhang, Kimball; Gershon, Andrea S.; Licskai, Christopher
Recent Global Initiative for Asthma (GINA) recommendations reduce the role of short-acting β2 -agonist (SABA) premised on the associated exacerbation risk. The widely accepted SABA risk profile is based on limited data described 30 years ago. This GINA paradigm shift demands an examination of SABA risks in a modern therapeutic era. Recent studies confirm that SABA overuse is common and associated with adverse outcomes. This study aimed to determine associations between SABA use, all-cause mortality and asthma exacerbations in an older North American asthma population. In this population-based cohort study, individuals with prevalent asthma (2006–2015) aged ≥65 years, eligible for provincial drug coverage, were included. Annual SABA canisters filled (0, 1–2, 3–5, ≥6) was the primary exposure. Hazard ratios (HRs) with 95% CIs were estimated using Cox proportional hazard regression, adjusted for confounders. There were 59 533 asthma individuals; 14% overused SABA (≥3 canisters annually). Compared to those who used <3 canisters, the adjusted HRs of death for those who used 3–5 and ≥6 canisters were 1.11 (95% CI: 1.02–1.22, p=0.0157) and 1.56 (95% CI: 1.41–1.71, p<0.0001), respectively. Severe asthma exacerbation rates for ≥3 and <3 canisters/year were 7.5% and 2.1%, respectively. The adjusted HRs of severe asthma exacerbations were 1.59 (95% CI: 1.40–1.82, p<0.0001) and 2.26 (95% CI: 1.96–2.60, p<0.0001) in those who used 3–5 and ≥6 SABA canisters per year, respectively. In Canada, 1 in 7 individuals with asthma overused SABA associated with increased risks of severe asthma exacerbations and death. The adverse impacts of SABA overuse continue 30 years after early publications. These results in older people with asthma add strength to previously documented associations of SABA use, severe asthma exacerbations and death. Clinicians may consider these safety results when prescribing and assessing new therapeutic recommendations. https://bit.ly/34Gr56P